Food security, farming, and climate change to 2050: Scenarios, results, policy options - Nelson, Gerald C.; Rosegrant, Mark W.; Palazzo, Amanda; Gray, Ian; Ingersoll, Christina; Robertson, Richard D.; Tokgoz, Simla; Zhu, Tingju; Sulser, Timothy B.; Ringler, Claudia; Msangi, Siwa; You, Liangzhi (International Food Policy Research Institute, 2010)
The first decade of the 21st century has seen several harbingers of a troubled future for global food security. The food price spike of 2008, with its consequent food riots and resulting political changes in several countries, awoke the world’s leaders to the re-emergence of this threat to human well-being and social harmony. The excessive heat and drought in Russia that led to the 2010 wildfires and grain embargo, as well as the unprecedented floods in Pakistan, signal more trouble ahead. But the warning signs could already be seen in the 1990s, as the long-term decline in the number of the world’s poor and hungry stalled, and those numbers began to rise. The seeds for these challenges, both for good and ill, were planted along with the Green Revolution crops in the mid-1960s. Dramatic increases in food production and land productivity led to complacency about the remaining challenges ahead, resulting in reduced public sector investments in agricultural productivity. Population numbers continue their march towards a likely 9 billion by 2050, while higher incomes in hitherto poor countries will lead to increased demand, which in turn puts additional pressures on sustainable food production.